RADEC: SEBUAH ALTERNATIF MODEL DALAM MENGEMBANGKAN PEMAHAMAN KONSEP IPA SISWA KELAS V SEKOLAH DASAR - Asep Nurhuda; Hany Handayani; Atep Lesmana; Annisa Nurfitriani; Ihsan Rizali; Gemi Gustiani; Reynitha Elfariani Suryadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This research was motivated by the low understanding of science concepts in elementary school students. This study aims to describe an increase in understanding of science concepts learned using the RADEC model (Read, Answers, Discuss, Explain and Create). This research is a quantitative research with quasi-experimental methods and uses pretest and posttest research designs. The object of this study is all grade V students of SDN 2 Bunder-Purwakarta for the 2022 / 2023 school year, the number of 2 classes each class consists of 32 students. Data collection techniques use tests, questionnaires, observations and documentation. Instruments to measure students' understanding of science concepts using pretests and posttests. The findings of the researchers that the model used has not been said to have an effect on increasing the understanding of the concept of science class V because of the strength of the two models used in learning, And also because of the low interest in reading students who are not used to looking for theoretical information first before being discussed by the teacher, this RADEC model plays a role for students to be more independent and active so that both teachers and students can both learn and teachers as facilitators. This is evidenced by the results of the n-gain test which shows almost the same average value. However, this radec learning model can create a conducive classroom atmosphere and students can play an active role in their classes and can increase student learning motivation, it can be seen from the scores that students get the average posttest results of experimental classes of 94 with the lowest score of 90 and the highest 100. While the posttest control class had an average score of 91 with the smallest score of 72 and a higher score of 98.